New perspectives in the course of treatment of catamenial epilepsy - Gulnaraa, Rakhimbaeva S. (International Journal of Psychosocial Rehabilitation, 2020)
Background.Catamenial epilepsy occurs in 5% of all women suffering from epilepsy. Here, the appearance of epileptic seizures is facilitated by hormonal disorders (changes in the ratio of estrogens/progesterone), violations of the water-electrolyte balance, a decrease in the level of antiepileptic drugs in the blood, premenstrual stress. During cyclic changes occurring in the ovaries, a statistically significant positive equivalence between estradiol and progesterone in serum was revealed. Premenstrual exacerbation of seizures was associated with the rapid extinction of the anticonvulsant action of progesterone. According to studies in female animal models, progesterone has been found to inhibit neuronal arousal and reduce spontaneous epileptic discharges. Ovariectomy in adult female rats is tantamount to a menopausal condition, and has been associated with increased convulsive activity. These rats showed faster progression of epileptic status compared to intact animals. The aim of this study is to present preclinical and clinical data on the relationship between female reproductive steroids and epileptic seizures, and to describe approaches to the treatment of catamenial epilepsy. In our study, we recommend monotherapy – topiramate, in order to reduce the risk of teratogenic effects on the fetus, in case of pregnancy. Material and methods: The study included 60 women with catamenial epilepsy (CE). The control group consisted of 20 women with symptomatic epilepsy that did not have a cyclic course. We studied the fluctuation of women sex hormones in women with catamenial epilepsy in the follicular and luteal phases of the cycle. The study of the dynamics of changes was based on the assessment of menstruation and seizures for at least two cycles. The number of attacks in each phase was counted. Results: As our studies have shown, fluctuations in estrogen and progesterone are noted in the follicular phase of the menstrual cycle. To optimize therapy, we replaced the anticonvulsant drug Carbamazepine with topiramate at the rate of 3-5 mg / kg body weight per day. Moreover, the average daily dose did not exceed 200 mg / day. The duration of monitoring the effectiveness of therapy was 6 months. Over this period, we noted a positive trend during catamenial epilepsy, which was expressed in a decrease in the frequency and duration of seizures, and in 28% of cases we noted a state of clinical remission, i.e. no attacks were observed during the observation period.